The Relationship Between Mastery of Linguistic Rules and Academic Reading Literacy with The Ability to Write Expository Texts of Engineering Students - Muhammad Zulfadhli; Laely Farokhah; Dwi Novia Al Husaeni (Universitas Negeri Surabaya, 2026)
The ability to write expository text is an important academic skill because it is related to the ability to convey ideas, data, and arguments logically and objectively. This study aims to analyze the relationship between reading literacy and mastery of language rules with the ability to write expository text. This study used a quantitative approach with a correlational design. The participants were 173 engineering students. Data were collected through a reading literacy questionnaire, a language rule mastery test, and an expository text writing test. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results showed that students' reading literacy, language rule mastery, and expository text writing ability tended to be high. However, reading literacy did not have a significant relationship with the ability to write expository text. Mastery of language rules also did not have a significant relationship with the ability to write expository text. The regression results showed that both independent variables simultaneously were not significant predictors of the ability to write expository text. This finding suggests that the ability to write expository text needs to be explained through other factors, such as argumentation skills, writing experience, and directed academic writing practices.